Onset of Internally Heated Convection in a Porous Layer With Variable Gravity: A Brinkmann Model - Venkateshwar Rao, M.; Lokapavani; Pavan Kumar Reddy, M.; Raghavendra, P. (Communications in Mathematics and Applications, 2023)
The influence of heat source, and variable gravity field on the stability of convective phenomena in a porous layer is investigated numerically by considering Brinkmann’s model. Three types of gravity variations, such as, linear, parabolic, and cubic functions are considered. For linear theory, the method of normal modes has been employed to solve governing dimensionless equations which led an eigenvalue problem. The onset of convection is delayed by increasing Darcy number and gravity variation parameter. An enhancement of internal heat source makes the system unstable.